2011
DOI: 10.1152/ajpregu.00736.2009
|View full text |Cite
|
Sign up to set email alerts
|

Nuclear membrane receptors for ET-1 in cardiovascular function

Abstract: Plasma membrane endothelin type A (ET(A)) receptors are internalized and recycled to the plasma membrane, whereas endothelin type B (ET(B)) receptors undergo degradation and subsequent nuclear translocation. Recent studies show that G protein-coupled receptors (GPCRs) and ion transporters are also present and functional at the nuclear membranes of many cell types. Similarly to other GPCRs, ET(A) and ET(B) are present at both the plasma and nuclear membranes of several cardiovascular cell types, including human… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
35
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(44 citation statements)
references
References 82 publications
9
35
0
Order By: Relevance
“…Intracrine signalling refers to a process whereby a ligand, originating within a target cell or taken up from the extracellular milieu, acts upon an intracellular receptor (reviewed in [9][10][11][62][63][64][65][66][67]). The origin of the ligand for endogenous endothelin receptors remains unknown.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Intracrine signalling refers to a process whereby a ligand, originating within a target cell or taken up from the extracellular milieu, acts upon an intracellular receptor (reviewed in [9][10][11][62][63][64][65][66][67]). The origin of the ligand for endogenous endothelin receptors remains unknown.…”
Section: Discussionmentioning
confidence: 99%
“…However, endothelin receptors, as well as several other GPCRs and their effectors, are also present on cardiac nuclear membranes (reviewed in [9][10][11]). Immunocytofluorescence studies have revealed ETA to be primarily in the plasma membrane with some perinuclear staining, whereas ETB localize to the nuclear membrane in ventricular myocytes [12,13].…”
Section: Introductionmentioning
confidence: 99%
“…ET-1 acts also as an intracrine, activating intracellular cognate receptors (2). Stimulation of ET-1 receptors at the plasma or nuclear membrane induces Ca 2ϩ release, NO, and reactive oxygen species formation in the cytosol or nucleus (5,30). Cardiovascular disease pathogenesis involves oxidative stress and further alteration of ET-1 and NO signaling pathways (30, 31).…”
Section: Discussionmentioning
confidence: 99%
“…In the cardiovascular human and rodent cells, ET A and ET B are localized to the plasma membrane, cytoplasm, nuclear membranes, and nucleoplasm (4 -6). ET-1 elevates both cytosolic and nuclear Ca 2ϩ concentrations; the rise in cysotolic Ca 2ϩ concentration, [Ca 2ϩ ] i , in response to ET-1 is seen in both intact and membrane-perforated cells (5). Moreover, ET-1 is involved in nitric oxide (NO) and reactive oxygen species generation both in the cytosol and in the nucleus (5).…”
Section: Endothelin-1 Exerts Its Actions Via Activation Of Et a And Et Bmentioning
confidence: 99%
See 1 more Smart Citation